2009
DOI: 10.1016/j.neuron.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Primitives for Motor Adaptation Reflect Correlated Neural Tuning to Position and Velocity

Abstract: The motor commands required to control voluntary movements under various environmental conditions may be formed by adaptively combining a fixed set of motor primitives. Since this motor output must contend with state-dependent physical dynamics during movement, these primitives are thought to depend on the position and velocity of motion. Using a recently developed "error-clamp" technique, we measured the fine temporal structure of changes in motor output during adaptation. Interestingly, these measurements re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
144
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(168 citation statements)
references
References 66 publications
23
144
1
Order By: Relevance
“…To quantify the degree of motor adaptation when changing movement directions of both arms (see Fig. 1B for the definition of "movement direction"), we used the "error-clamp" method (Scheidt et al, 2000;Smith et al, 2006;Sing et al, 2009). During error-clamped trials, the trajectory of the handle was constrained to a straight line toward the target by a virtual "channel" (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To quantify the degree of motor adaptation when changing movement directions of both arms (see Fig. 1B for the definition of "movement direction"), we used the "error-clamp" method (Scheidt et al, 2000;Smith et al, 2006;Sing et al, 2009). During error-clamped trials, the trajectory of the handle was constrained to a straight line toward the target by a virtual "channel" (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of unimanual reaching movement have suggested that the brain accomplishes flexible movements by constructing an "internal model" of the dynamic properties of the body and the environment (Kawato, 1989;Bhushan and Shadmehr, 1999). It was also suggested that humans build these internal models through a flexible combination of motor primitives encoding the kinematics of the desired arm (Thoroughman and Shadmehr, 2000;Donchin et al, 2003;Sing et al, 2009). However, this powerful scheme is not directly compatible with control of bimanual movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The session on the last day consisted of continuing exposure to the horizontal/vertical force fields, interspersed with four probing batches. Each probing batch (always preceded by a 10 trial washout) consisted of 20 probing "triplets" (Sing et al, 2009) with three to five washout trials in between. Each triplet consisted of an error-clamp trial without any additional force field, followed by a velocity-dependent force field trial with a force in one of the four diagonal direction and a gain of 5 N ⅐ s/m, and another errorclamp trial without additional force field.…”
Section: Methodsmentioning
confidence: 99%
“…On the third day, we tested how subjects adapted to diagonal force fields by using triplets of trials, consisting of a diagonal force field trial with the gain of 5 N ⅐ s/m, sandwiched between two error-clamp trials (Sing et al, 2009). These triplets were separated by three to five washout trials (no force, no error clamp), and every subject experienced 80 triplets in total, with 20 triplets using forces in each diagonal direction.…”
Section: Experiments 3: Force Fieldsmentioning
confidence: 99%